Tumor-Infiltrating iNKT Cells Activated through c-Kit/Sca-1 Are Induced by Pentoxifylline, Norcantharidin, and Their Mixtures for Killing Murine Melanoma Cells - Maximiliano V. M. Correa-Lara; Israel Lara-Vega; Minerva Nájera-Martínez; María Lilia Domínguez-López; Elba Reyes-Maldonado; Armando Vega-López (MDPI AG, 2023)
The involvement of NK and other cytotoxic cells is considered the first defense line against cancer. However, a significant lack of information prevails on the possible roles played by factors considered characteristic of primitive cells, such as c-kit and Sca-1, in activating these cells, particularly in melanoma models subjected to treatments with substances under investigation, such as the case of norcantharidin. In this study, B16F1 murine melanoma cells were used to induce tumors in DBA/2 mice, estimating the proportions of NK and iNKT cells; the presence of activation (CD107a+) and primitive/activation (c-kit+/Lya6A+) markers and some tumor parameters, such as the presence of mitotic bodies, nuclear factor area, NK and iNKT cell infiltration in the tumor, infiltrated tumor area, and infiltrating lymphocyte count at 10x and 40x in specimens treated with pentoxifylline, norcantharidin, and the combination of both drugs. Possible correlations were estimated with Pearson's correlation analysis. It should be noted that, despite having demonstrated multiple correlations, immaturity/activation markers were related to these cells' activation. At the tumor site, iNKT cells are the ones that exert the cytotoxic potential on tumor cells, but they are confined to specific sites in the tumor. Due to the higher number of interactions of natural killer cells with tumor cells, it is concluded that the most effective treatment was PTX at 60 mg/kg + NCTD at 0.75 mg/kg.